Risk Management Analysis to Minimize the Occurrence of Fraud in ATM Machine Activities (A Study at XY Company in the Jakarta Area) - Mahardinata, Panji; Imaroh, Tukhas Shilul (Universitas Mercu Buana, 2025)
This study aims to analyze and detect the factors influencing fraud occurrences in ATMs at XY Company and evaluate the risk management strategies implemented to minimize such risks. This research employs a qualitative method with a descriptive approach and utilizes purposive sampling in the selection of informants. The study focuses on a state-owned bank, XY Company, located in the Jakarta area. Data was collected through interviews with four informants from XY Company, each with different job backgrounds, as well as through observations and documentation related to fraud cases that occurred between 2021 and 2023, totaling 240 cases. The findings indicate that ATM fraud at XY Company is caused by several factors, including weaknesses in the security system, low customer awareness of fraud modus operandi, and limited supervision of suspicious activities. Common types of fraud include skimming, card trapping, and jackpotting, which are executed through various technological manipulation techniques and social engineering tactics targeting customers. To mitigate fraud, XY Company has implemented various risk management strategies, such as enhancing technology-based supervision through the use of chip cards and real-time transaction monitoring. The conclusion of this study emphasizes that the implementation of stringent security systems, technology-based monitoring, and continuous customer education are key measures in combating ATM fraud. With effective risk management strategies, XY Company can reduce fraud crime rates and enhance customer trust in banking services.